Liposomal doxorubicin doubly functionalized with CCK8 and R8 peptide sequences for selective intracellular drug delivery1. (6th March 2015) - Ringhieri, Paola; Diaferia, Carlo; Galdiero, Stefania; Palumbo, Rosanna; Morelli, Giancarlo; Accardo, Antonella; Morelli, Giancarlo
<x xml:space="preserve">Abstract</x> A new dual‐ligand liposomal doxorubicin delivery system, which couples targeting to enhanced cellular uptake and may lead to a more efficient drug delivery system, is here designed and synthetized. Liposomes based on the composition 1, 2‐dioleoyl‐sn‐glycero‐3‐phosphocholine/1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐Peg2000‐R8/(C18)2‐L5‐SS‐CCK8 (87/8/5 mol/mol/mol) were prepared and loaded with doxorubicin. Presence of the two peptides on the external surface is demonstrated by fluorescence resonance energy transfer assay. The combination of the R8 cell‐penetrating peptide and of the CCK8 targeting peptide (homing peptide) on the liposome surface is obtained by combining pre‐modification and post‐modification methods. In the dual‐ligand system, the CCK8 peptide is anchored to the liposome surface by using a disulfide bond. This chemical function is inserted in order to promote the selective cleavage of the homing peptide under the reductive conditions expected in proximity of the tumor site, thus allowing targeting and internalization of the liposomal drug. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.